2011
DOI: 10.1074/jbc.m110.187948
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Tuning in Sensory Rhodopsin I from Salinibacter ruber

Abstract: Organisms utilize light as energy sources and as signals. Rhodopsins, which have seven transmembrane ␣-helices with retinal covalently linked to a conserved Lys residue, are found in various organisms as distant in evolution as bacteria, archaea, and eukarya. One of the most notable properties of rhodopsin molecules is the large variation in their absorption spectrum. Sensory rhodopsin I (SRI) and sensory rhodopsin II (SRII) function as photosensors and have similar properties (retinal composition, photocycle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…Similar to the spectral shift of the A223T mutant of HwBR (437 cm Ϫ1 ), it has already been reported that an Ala to Thr or Thr to Ala mutation at position 223 causes a spectral blue shift in HsBR and SRI or a red shift in SRII, respectively, with similar shift values (⌬ ϭ 356 -545 cm Ϫ1 ) (15,17,34), confirming that this residue is one of the important color-tuning residues in microbial rhodopsins. In the case of the residues Asp-123 and Ser-149, their contributions to the color tuning have also been reported in mutants of HsBR, SRI, and SRII (15,17,19). For Met-126, however, the shift value caused by the M118A mutation in HsBR was 3284 cm Ϫ1 (19), which is much larger than those of both HwBR (300 cm Ϫ1 ), AR3 (541 cm Ϫ1 ), and SRII (160 cm Ϫ1 ) (15).…”
Section: Color-tuning Mechanism In Proton Pumpingsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar to the spectral shift of the A223T mutant of HwBR (437 cm Ϫ1 ), it has already been reported that an Ala to Thr or Thr to Ala mutation at position 223 causes a spectral blue shift in HsBR and SRI or a red shift in SRII, respectively, with similar shift values (⌬ ϭ 356 -545 cm Ϫ1 ) (15,17,34), confirming that this residue is one of the important color-tuning residues in microbial rhodopsins. In the case of the residues Asp-123 and Ser-149, their contributions to the color tuning have also been reported in mutants of HsBR, SRI, and SRII (15,17,19). For Met-126, however, the shift value caused by the M118A mutation in HsBR was 3284 cm Ϫ1 (19), which is much larger than those of both HwBR (300 cm Ϫ1 ), AR3 (541 cm Ϫ1 ), and SRII (160 cm Ϫ1 ) (15).…”
Section: Color-tuning Mechanism In Proton Pumpingsupporting
confidence: 57%
“…In those studies that aimed to determine the key residue(s) contributing to the color change of SRII, several SRII mutants were analyzed in which each residue was replaced by its corresponding residue in BR. In addition to this, we also performed similar experiments for SRI (17). From the results, we have found the key residues (factors) contributing to the color change from orange (ϳ500 nm) to purple (ϳ560 nm), as well as several unique factors, as the interaction between the Dand E-helices for SRII (16) or the chloride ion binding around the ␤-ionone ring for SRI (18), respectively.…”
mentioning
confidence: 85%
“…By replacing single amino acid residues in Salinibacter ruber sensory rhodopsin I (SrSRI, λ max = 557 nm) with the corresponding residues from Natronomonas pharaonis sensory rhodopsin II (NpSRII, λ max = 498 nm, ~30% amino acid identity to SrSRI), Sudo et al identified three blue tuning mutations, each of which shifted λ max by 14-24 nm [27]. The SrSRI variant with all three mutations had a λ max of 525 nm (32 nm blue shift), accounting for more than half the spectral shift between SrSRI and NpSRII [27].…”
Section: Random Mutagenesis and Screening Of Monterey Bay Proteorhodomentioning
confidence: 99%
“…By replacing single amino acid residues in Salinibacter ruber sensory rhodopsin I (SrSRI, λ max = 557 nm) with the corresponding residues from Natronomonas pharaonis sensory rhodopsin II (NpSRII, λ max = 498 nm, ~30% amino acid identity to SrSRI), Sudo et al identified three blue tuning mutations, each of which shifted λ max by 14-24 nm [27]. The SrSRI variant with all three mutations had a λ max of 525 nm (32 nm blue shift), accounting for more than half the spectral shift between SrSRI and NpSRII [27]. In ChRs, recombination of variants with different spectral preferences, kinetics, and ion permeability has been used to generate mutants with different combinations of these properties [28], including a highly active red-shifted mutant called ReaChR [29].…”
Section: Random Mutagenesis and Screening Of Monterey Bay Proteorhodomentioning
confidence: 99%
“…In general, the absorption maximum is related to the wavelength of light in environments where the organisms are living. We have previously identified the residues responsible for the color-tuning among various microbial rhodopsins, such as BR, HwBR, AR3, and sensory rhodopsin I (SRI), which show the color purple, and such as sensory rhodopsin II (SRII) and middle rhodopsin, which show the color orange (41)(42)(43)(44). On the basis of these results, we speculate that Ser-129 (in helix-D) as well as Phe-159 and Tyr-164 (both in helix-E) (Fig.…”
Section: Similarities and Dissimilarities Between Tr And Other Microbmentioning
confidence: 99%